Підприємництво в структурі Національної інноваційної системи - Фрідман, Олена Анатоліївна; Fridman, О.А. (Харків : Харківський національний університет імені В.Н. Каразіна, 2021)
Інноваційний розвиток в сучасних умовах – це актуальна потреба. Традиційні засоби діяльності трансформуються, фірма з класичного підприємства перетворюється в складну мережеву структуру, стає частиною цифрової бізнес-системи. Національна система інноваційного підприємництва охоплює всі стадії інтегрованого інноваційного процесу і сфери інноваційної діяльності та забезпечує його спрямування на досягнення цілей інноваційного розвитку економіки країни. В цифровій бізнес екосистемі змінюються структури підприємницької діяльності, здійснюється перехід до мережевої економіки, економіки знань, що продукує постійні інновації. Поступово підприємництво, у тому числі й інноваційне, стає цифровим.

In this thesis, I prove that innovative development is an urgent need in modern conditions caused by historic, economic, environmental, social and political factors. It is a response to modern challenges, a field to realize human culture and human intellectual potential. Innovative entrepreneurship is the core of the innovation system which can quickly respond to changes and effectively solve complex problems, increase national competitiveness and improve welfare of the population. The processes of improving innovative entrepreneurship are to be considered in their interrelation with forming and functioning of the national system of innovative entrepreneurship. I identify the main characteristics of the national system of innovative entrepreneurship seen as an organizational and economic form of entrepreneurship covering all stages of an integrated innovation process and innovation sphere and ensuring its direction towards achieving the country’s development goals by defining the functions of innovations capitalization based on investment in intellectual products in accordance with their life cycle stages and socialization of innovations and innovative entrepreneurship. In view of this, the study of innovative entrepreneurship and substantiation on this basis of conceptual foundations of improving the state’s economic policy aimed at strengthening the national system of innovative entrepreneurship has an important theoretical and practical value.
Entrepreneurship in the Structure of the National Innovation System
Keywords: SOCIAL SCIENCES::Business and economics::Economics; цифрова економіка; інновації; інноваційне підприємництво; інституційне середовище; національна інноваційна система; digital economy; innovations; innovative entrepreneurship; innovative type of development; institutional environment; national innovation system